2021
DOI: 10.1002/essoar.10506215.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Martian crustal field influence on O+ and O2+ escape as measured by MAVEN

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The third difference is that Mars possesses localized intense crustal fields, which could organize the plasma dynamics (e.g., Soobiah et al, 2013Soobiah et al, , 2019Weber et al, 2021). Here we provide several possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The third difference is that Mars possesses localized intense crustal fields, which could organize the plasma dynamics (e.g., Soobiah et al, 2013Soobiah et al, , 2019Weber et al, 2021). Here we provide several possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, a detailed explanation of the complex dependence of the Martian magnetotail escape rate on the local magnetic field is beyond the scope of this study. Weber et al (2021) suggested that the presence of a local-scale magnetic shielding suppresses local ion escape in some cases by up to 80%. An analysis of the statistical results by Lundin et al (2011) suggests that dayside "mini-magnetospheres" can play an important role in reducing tail transport and escape of the ionospheric plasma.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Thus, we can extrapolate that the small escape rate for the high magnetic field intensity is due to the enhanced shielding of the ionosphere by the local fields. Furthermore, the local crustal fields that normally withstand solar wind erosion may be completely overwhelmed during periods of increased solar wind pressure (Weber et al, 2021), which could explain the greater effect on ion escape of the solar wind dynamic pressure than the local magnetic fields.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Precipitation of electrons along the open field lines produce discrete aurora typical for the Earth magnetosphere (Girazian et al, 2021;Lillis et al, 2018;Schneider et al, 2021). It is worth noting that crustal magnetic fields on Mars not only change the field topology but also significantly vary the density distribution in the upper ionosphere (Andrews et al, 2013;Dubinin et al, 2012Dubinin et al, , 2016 and influence the ion loss (Dubinin, Fraenz, et al, 2020;Fan et al, 2019Fan et al, , 2020Fang et al, 2015Fang et al, , 2017Weber et al, 2021).…”
Section: Introductionmentioning
confidence: 99%